Designing a deposit-refund system for cigarette butts: What do smokers care about? - Fivita Stri; Takuro Uehara; Takahiro Tsuge; Sitadhira Prima Citta; Misuzu Asari (PLoS ONE, 2025)
Cigarette butts (CBs) are the world’s most littered item and significantly contribute to environmental pollution. A deposit-refund system (DRS) has been proposed to reduce CB littering, but its effective design remains underexplored. This study addressed this gap by investigating smokers’ perceptions and preferences in hypothetical DRS scenarios for CBs. We conducted a discrete choice experiment in Japan (n = 1,865) and Indonesia (n = 2,000). Respondents were divided into treatment and control groups, with the treatment group receiving information on CB environmental impact aligned with the WHO’s campaign. Our results revealed that a DRS for CBs was preferred to the status quo, with higher preferences in Indonesia (90.33%) than in Japan (63.92%). The information treatment further increased DRS preferences (Indonesia: 91.82%; Japan: 69.83%) and willingness to endure cost to support DRS operations. Cost simulations showed participation probabilities remained above 55% with a cost of up to 5% of a cigarette’s price in Japan, and above 80% with a cost of up to 10% in Indonesia. Our findings underscore the importance of environmental information in DRS adoption. Both countries preferred a producer-managed system to a government-managed one, highlighting an opportunity for tobacco producers to fulfill extended producer responsibility through a DRS. Furthermore, DRS design should be country-specific. Notably, Japanese respondents’ familiarity with heat-not-burn cigarettes influenced their preference for a tailored DRS to those products, whereas Indonesian respondents preferred a DRS for CBs. Japanese respondents also emphasized accessibility more than their Indonesian counterparts.